2021
DOI: 10.3389/fphys.2021.681370
|View full text |Cite
|
Sign up to set email alerts
|

Are Static and Dynamic Postural Balance Assessments Two Sides of the Same Coin? A Cross-Sectional Study in the Older Adults

Abstract: The aim of this study was to investigate if the combination of static and dynamic postural balance assessments gives more accurate indications on balance performance among healthy older adults. We also aimed at studying the effect of a dual-task condition on static and dynamic postural balance control. Fifty-seven healthy older adults (age = 73.2 ± 5.0 year, height = 1.66 ± 0.08 m, and body mass = 72.8 ± 13.8 kg) completed the study. Static and dynamic balance were assessed both in single-task and dual-task co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…Indeed, OS displayed a worse FB and GB than the young cohorts and a worse FiB than YA. Although no differences were detected between OA and all the other groups, in a previous study (Marcolin et al, 2021), including a sub-set of the present sample, significant differences comparing only OA and OS emerged for all the DPBC parameters with large effects sizes.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Indeed, OS displayed a worse FB and GB than the young cohorts and a worse FiB than YA. Although no differences were detected between OA and all the other groups, in a previous study (Marcolin et al, 2021), including a sub-set of the present sample, significant differences comparing only OA and OS emerged for all the DPBC parameters with large effects sizes.…”
Section: Discussioncontrasting
confidence: 84%
“…A sub-set of the present SPBC and DPBC datasets presented in this work has been presented elsewhere (Sarto et al, 2020;Marcolin et al, 2021). Participants have been asked to visit the laboratory twice.…”
Section: Protocolmentioning
confidence: 99%
“…However, as balance degrades with age, strength and the ability to precisely control handgrip force are also well known to decrease with age. In addition, dynamic balance and handgrip strength seem to be correlated ( 49 ), and we could expect a correlation that is worth investigating in future studies, also with a lifespan approach.…”
Section: Discussionmentioning
confidence: 95%
“…This is not an entirely new finding. Previous studies have shown only weak correlations between static and dynamic balance tests in older adults ( Rizzato et al, 2021 ), and the selective improvement of dynamic balance and gait outcomes, as opposed to the absence of significant improvement in static balance, was reported in patients with peripheral neuropathy of the lower limbs treated with physiotherapy ( Caronni et al, 2019 ). It can be proposed that static balance, heavily based on high-frequency neural adjustments, can be more difficult to maintain, compared to dynamic balance, heavily based on low-frequency anticipatory actions and, at least in walking, profiting from passive pendulum-like oscillations and inertial stabilization.…”
Section: Discussionmentioning
confidence: 99%